Comparative study between animal cheese and similar vegetable: physicochemical, microbiological and sensory aspects (Research, Society and Development, 2020)
Minas Frescal cheese has wide acceptance and it is part of many Brazilians' typical diet. However, it was observed that there is an increase in the search for similar products of vegetable origin, due to health problems related to the intake of dairy products. This research aimed to evaluate the potential replacement of Minas cheese by the similar vegetable cheese - tofu. Two brands of Minas Frescal Cheese (MC) and two of similar vegetable product (VS) (tofu), were assessed based on microbiological, physicochemical and sensory parameters. All samples are in accordance with the microbiological standards of Brazilian law. The pH was around 6.0. The samples MC1 and MC2 had high levels of acidity and lipids, while the VS1 and VS2 had high levels of protein. Samples with high moisture content were also the least firm (VS1 and MC1).The general acceptance of  attributes was satisfactory for samples MC1 and MC2, which would be bought and consumed, while the opposite was true  with VS1 and VS2. All samples were considered to have a salt level below the ideal level. The samples MC1 and VS1 assessed were less firm than the ideal level, while samples MC2 and VS2 were firmer than the ideal level. Tofu was not accepted as a substitute for Minas Frescal Cheese by consumers. It requires optimization of texture and salt level in order to fulfill this purpose. However, Tofu presented an advantage in relation to its low fat level and high protein level.